URGENSI PENGELOLAAN KELAS DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMA NEGERI 15 BULUKUMBA - Suardi M Suardi M (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
This study aims to determine how and what is the urgency class management class management in improving students' motivation in SMAN 15 Bulukumba. The approach taken in this study is a qualitative study using the method of collecting data through field research by observation and interviews. The data obtained were processed and analyzed through three grooves, namely data reduction, data display (presentation) and verification of data. The research found that the management class at SMAN 15 Bulukumba refer to the components of classroom management skills ie skills related to the creation and maintenance of optimal learning conditions and Skills attention is by way of visual and verbal. Motivation for students at SMAN 15 Bulukumba influenced by factors intrinsic, motivation arises naturally from within the residual and extrinsic motivation that arise because of the effect the ability of teachers to manage the classroom. Urgency classroom management in improving students' motivation in SMAN 15 Bulukumba to see some of the constraints faced by the lack of school facilities that support the learning process such as the media images and other displays. In addition, some teachers lack skills in managing the classroom so that the classroom atmosphere becomes monotonous.